The Association Between PTSD and Functional Outcome Is Mediated by Perception of Cognitive Problems Rather Than Objective Neuropsychological Test Performance. Issue 5 (14th October 2017) - Samuelson, Kristin W.; Abadjian, Linda; Jordan, Joshua T.; Bartel, Alisa; Vasterling, Jennifer; Seal, Karen
Abstract: Posttraumatic stress disorder (PTSD) has been consistently linked to poorer functional outcomes, including quality of life, health problems, and social and occupational functioning. Less is known about the potential mechanisms by which PTSD leads to poorer functional outcomes. We hypothesized that neurocognitive functioning and perception of cognitive problems would both mediate the relationship between PTSD diagnosis and functioning. In a sample of 140 veterans of the recent wars and conflicts in Iraq and Afghanistan, we assessed PTSD symptoms, history of traumatic brain injury (TBI), depression, self‐report measures of quality of life, social and occupational functioning, and reintegration to civilian life, as well as perception of cognitive problems. Veterans also completed a comprehensive neuropsychological battery of tests. Structural equation modeling revealed that perception of cognitive problems, but not objective neuropsychological performance, mediated the relationship between PTSD diagnosis and functional outcomes after controlling for TBI, depression, education, and a premorbid IQ estimate, b = −6.29, 95% bias‐corrected bootstrapped confidence interval [−11.03, −2.88], showing a large effect size. These results highlight the importance of addressing appraisals of posttrauma cognitive functioning in treatment as a means of improving functional outcomes.